THE EXISTENCE OF THE GOVERNOR'S SUPERVISION OF REGIONAL REGULATIONS AND REGIONAL HEAD REGULATIONS OF REGENCY/CITY IN THE UNITED STATE OF THE REPUBLIC OF INDONESIA - Raymoon Brando Edwin Tampemawa (AIBPM Publisher, 2022)
The role of the Governor as a representative of the Government in this era of broad autonomy is very strategic, where as the holder of the mandate from the President to oversee Regional Regulations and Regional Head Regulations of Regency/City need to be strengthened. After the Constitutional Court Decision Number 137/PUU-XIII/2015, Minister of Home Affairs Regulation Number 120 of 2018, which essentially regulates the addition of Verification in preventive supervision, and changes in form from Cancellation to Clarification in repressive supervision. However, with the amendment of Article 251 of Law Number 23 of 2014 through Article 176 Point 3 of Law Number 11 of 2020, repressive supervision is no longer known. In contrast to Law Number 1 of 2022, repressive supervision of Regional Regulations concerning Regional Taxes and Levies is regulated, but it is no longer the authority of the Governor, but has been handled directly by the Central Government. This fact of legal norms weakens the existence of the Governor's supervision of Regional Regulations and Regional Head Regulations of Regency/City, so that an ideal concept is needed in the form of structural integration; through the establishment of regional regulatory bodies, as well as substantially; through the implementation of integrated supervisory regulations under the coordination of regional regulatory agencies, which are managed digitally.Key words: Supervision; Local Regulation/Regional Head Regulation; Unitary State.